Formability Analysis of Crca-IS2 Sheet to Eliminates the Defects during Deep Draw - Singh, Satpal; Singh, Gurmeet; Singh, Simardeep (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947455);" role="presentation">Metal forming operations in industries are performed by the she<span dir="ltr" style="left: calc(var(--scale-factor)*337.39px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914323);" role="presentation">et metal processes. In sheet me<span dir="ltr" style="left: calc(var(--scale-factor)*466.78px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946768);" role="presentation">tal <span dir="ltr" style="left: calc(var(--scale-factor)*480.46px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971846);" role="presentation">work <span dir="ltr" style="left: calc(var(--scale-factor)*504.46px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.852173);" role="presentation">deep <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906969);" role="presentation">drawing plays a major role to form the desired shapes. <span dir="ltr" style="left: calc(var(--scale-factor)*291.65px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894902);" role="presentation">Improper design process leads to defected parts which are <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888005);" role="presentation">not acceptable due to <span dir="ltr" style="left: calc(var(--scale-factor)*159.26px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887173);" role="presentation">ergonomics as well as aesthetics. <span dir="ltr" style="left: calc(var(--scale-factor)*293.57px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899045);" role="presentation">Enormous defects during drawing have been discussed in <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*88.46px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975958);" role="presentation">literature. FEA of sheet met<span dir="ltr" style="left: calc(var(--scale-factor)*206.93px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964215);" role="presentation">al drawing was performed <span dir="ltr" style="left: calc(var(--scale-factor)*321.43px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951502);" role="presentation">by <span dir="ltr" style="left: calc(var(--scale-factor)*335.59px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969191);" role="presentation">using a blank. <span dir="ltr" style="left: calc(var(--scale-factor)*399.31px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968359);" role="presentation">During the drawing operation <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.998143);" role="presentation">wrink<span dir="ltr" style="left: calc(var(--scale-factor)*95.30px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971251);" role="presentation">ling and tearing were observed experimentally. FEA <span dir="ltr" style="left: calc(var(--scale-factor)*320.71px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.788658);" role="presentation">as <span dir="ltr" style="left: calc(var(--scale-factor)*333.43px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939497);" role="presentation">an e<span dir="ltr" style="left: calc(var(--scale-factor)*351.67px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981529);" role="presentation">ffective tool has been concluded for this <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896552);" role="presentation">technique. <span dir="ltr" style="left: calc(var(--scale-factor)*115.82px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946607);" role="presentation">The results will help in optimizing <span dir="ltr" style="left: calc(var(--scale-factor)*256.25px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892133);" role="presentation">the process by changing the input parameters <span dir="ltr" style="left: calc(var(--scale-factor)*439.27px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909312);" role="presentation">and help the industry <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*401.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927297);" role="presentation">to perform hit and trial on simulator rather than virtual environment